2021
DOI: 10.3390/cells10113208
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of CD19.CAR-T Cell Detection by Flow Cytometry and PCR

Abstract: Chimeric-antigen-receptor-T (CAR-T) cells are currently revolutionizing the field of cancer immunotherapy. Therefore, there is an urgent need for CAR-T cell monitoring by clinicians to assess cell expansion and persistence in patients. CAR-T cell manufacturers and researchers need to evaluate transduction efficiency and vector copy number for quality control. Here, CAR expression was analyzed in peripheral blood samples from patients and healthy donors by flow cytometry with four commercially available detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…Therefore, the survival of transgenic cells not expressing the CAR is unlikely. Accordingly, high correlation levels of CAR quantification data obtained by PCR-based approaches determining the transgene at the genomic level and FC detecting the CAR protein on the CAR T cell surface have been reported by our group ( 18 , 32 ) and others ( 10 ).…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, the survival of transgenic cells not expressing the CAR is unlikely. Accordingly, high correlation levels of CAR quantification data obtained by PCR-based approaches determining the transgene at the genomic level and FC detecting the CAR protein on the CAR T cell surface have been reported by our group ( 18 , 32 ) and others ( 10 ).…”
Section: Discussionsupporting
confidence: 63%
“…Jiali Cheng et al [1] answered positively this question, which has also been confirmed in previous studies [13, 14]. CAR T cell were efficiently detected by flow cytometry, especially using an anti‐idiotype antibody, with a LOD at 0.03678% of lymphocytes (mean + 3SD in healthy whole blood) with reasonable coefficient of variance below 11%. The next question constitutes the main objective of the study: Would flow cytometry compete with droplet digital PCR (dd‐RT PCR) efficiency in detecting rare CAR T cells? …”
Section: Figurementioning
confidence: 68%
“…This needs to be adapted to monitor new CAR programs using other cell types like NK cells [9,10] and other tumor types like solid tumors, for which, TAAs are highly variable [11,12]. Jiali Cheng et al [1] answered positively this question, which has also been confirmed in previous studies [13,14]. CAR T cell were efficiently detected by flow cytometry, especially using an anti-idiotype antibody, with a LOD at 0.03678% of lymphocytes (mean + 3SD in healthy whole blood) with reasonable coefficient of variance below 11%.…”
Section: Car T Cells Have An Initial Expansion Phase Upon Reinfusion Andmentioning
confidence: 68%
“…36 Moreover, given that the transduction efficiency and vector copy number of CAR-T-cells can be detected and evaluated by flow cytometry and qPCR, improvements in these technologies may be helpful to this problem. 122 Other solutions to enhance CAR-T efficacy For the CAR-T therapy for B-cell malignancies, investigators have explored a variety of methods to enhance the efficacy, such as combination strategies and dual-target CAR-T-cell therapy. 123,124 A preclinical study showed that the expression of PD-1 and PD-L1 was upregulated after CAR-T infusion, which will inhibit the effector function of CAR-T-cells.…”
Section: Solutions To Tumor Contaminationmentioning
confidence: 99%
“… 36 Moreover, given that the transduction efficiency and vector copy number of CAR-T-cells can be detected and evaluated by flow cytometry and qPCR, improvements in these technologies may be helpful to this problem. 122 …”
Section: Solutions To Overcome the Current Challenges And Enhance Eff...mentioning
confidence: 99%